2022
DOI: 10.1371/journal.pone.0277959
|View full text |Cite
|
Sign up to set email alerts
|

Validation of prognostic scores predicting mortality in acute liver decompensation or acute-on-chronic liver failure: A Thailand multicenter study

Abstract: Background & objectives Cirrhosis patients with worsening of the liver function are defined as acute decompensation (AD) and those who develop extrahepatic organ failure are defined as acute-on-chronic liver failure (ACLF). Both AD and ACLF have an extremely poor prognosis. However, information regarding prognostic predictors is still lacking in Asian populations. We aimed to identify prognostic factors for 30-day and 90-day mortality in cirrhosis patients who develop AD with or without ACLF. Methods We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(58 reference statements)
1
2
0
Order By: Relevance
“…The predictive ability of CLIF-C ACLFs is relatively low in predicting short-and long-term mortality in ACLF patients with a concomitant need for ICU treatment (24)(25)(26). However, the MELD score is the most predictive score (27). Our results con rm the ability of both scores in predicting ACLF development in these patients.…”
Section: Discussionsupporting
confidence: 77%
“…The predictive ability of CLIF-C ACLFs is relatively low in predicting short-and long-term mortality in ACLF patients with a concomitant need for ICU treatment (24)(25)(26). However, the MELD score is the most predictive score (27). Our results con rm the ability of both scores in predicting ACLF development in these patients.…”
Section: Discussionsupporting
confidence: 77%
“…In contrast, the CLIF-C OFs and the CLIF-C ACLFs performed worse in our study. A retrospective study from Thailand with over 600 patients with acute decompensation of liver cirrhosis was able to provide similar data [ 16 ]. Here, the CLIF-OF score also showed only a moderate predictive value in relation to the 30- and 90-day mortality.…”
Section: Discussionmentioning
confidence: 98%
“…However, in keeping with the EASL/American Association for the Study of Liver Diseases (AASLD) criteria, none of the three scores including MELD, Child–Pugh, and albumin-bilirubin (ALBI) were considerably related to the in-hospital mortality [ 34 ]. Another study found that compared with other scores, CLIF-C ACLFs had the highest AUROC in predicting 28-day mortality [ 35 ], while other studies reported that the predictive accuracy of CLIF-SOFAs and the simpler CLIF-C OFs for mortality were considerably higher than that of CLIF-C ACLFs and MELDs [ 36 , 37 ]. The CLIF-C OFs is a model that quantifies severity of organ dysfunction and calculates the sum to estimate the prognosis of ACLF.…”
Section: Discussionmentioning
confidence: 99%